Exploring Employment Rights for Individuals with Disabilities: A Cross-National Comparative Analysis in The Context of Fair Competition and Sustainable Development Goals - Rianda Dirkareshza; Sahda Saraswati Akbar; Gilang Abi Zaifa (Alauddin Law Development Journal (ALDEV), 2024)
Disabilities are defined as people who show functional difficulties along with the obstacles present from the social environment so as to limit their participation in society. This research aims to provide insight for policy makers, practitioners, and organizations that care about the rights of workers with disabilities in developing and improving existing regulations and policies. This study uses a comparative legal research method that compares existing regulations in Germany, Canada, Australia, Japan, and the US with existing regulations in Indonesia through a statutory law research and a conseptual approach. The novelty in this writing is to conduct a comparative study of the rights of workers with disabilities from 4 continents, especially with 6 different countries to create ideal regulatory and policy concepts that can be implemented in Indonesia. However, Indonesia itself has created a Disability Vocational Training Center (PPVD) which aims to empower disabled workers to welcome an inclusive Indonesia.